1999
DOI: 10.1046/j.1365-201x.1999.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Slower fatigue and faster recovery of the adductor pollicis muscle in women matched for strength with men

Abstract: In previous gender comparisons of muscle performance, men and women rarely have been closely matched, absolute force has not been equalized, and rates of fatigue and early recovery have not been determined. We compared adductor pollicis muscle performance at a similar absolute force development in healthy men and women (both n=9) matched for adductor pollicis maximal voluntary contraction (MVC) force (132 +/- 5 N for women and 136 +/- 4 N for men, mean +/- SE, P > 0.05). Subjects repeated static contractions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
114
3
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(145 citation statements)
references
References 30 publications
22
114
3
5
Order By: Relevance
“…Thus, the animals in fatigue task 1 ran substantially longer than those in fatigue task 2. There was a greater fatigue observed in females than male mice in the longer duration fatigue task (fatigue task 1), which was surprising given prior data showing fatigability is greater in males than in female human subjects (22,24,27,38,66). However, in human studies, differences in the development of muscle fatigue between sexes are task dependent (31).…”
Section: Fatigue Tasksmentioning
confidence: 41%
See 1 more Smart Citation
“…Thus, the animals in fatigue task 1 ran substantially longer than those in fatigue task 2. There was a greater fatigue observed in females than male mice in the longer duration fatigue task (fatigue task 1), which was surprising given prior data showing fatigability is greater in males than in female human subjects (22,24,27,38,66). However, in human studies, differences in the development of muscle fatigue between sexes are task dependent (31).…”
Section: Fatigue Tasksmentioning
confidence: 41%
“…In human subjects, males have greater overall strength, but can fatigue to a greater extent than females in a task-dependent manner (22,27,31). When males and females are matched for strength, women fatigued less than men during intermittent contractions but performed similarly during sustained low-intensity contractions as males (27).…”
mentioning
confidence: 99%
“…It has been documented that women have better endurance than men when performing static contractions of low or moderate intensity (39)(40)(41)(42). Hence the gender difference in endurance times during shoulder abduction is probably caused by the slightly higher relative force of the women.…”
Section: Discussionmentioning
confidence: 98%
“…Clark et al (2003)found that there is a 33% difference in muscular endurance capacity between males and females and a number of studies have found differences in the recovery time of males and females (Fulco et. al., 1999;Russ & KentBraun, 2003;Russ et al, 2005;Hunter et al, 2006).…”
Section: Hypothesesmentioning
confidence: 99%